To Study the Health-Related Quality of Life (HRQOL) in Children Presenting with Guillain-Barré Syndrome (GBS) in a Tertiary Care Hospital - Ambreen, Sara; Waris, Rehmana; Qayyum, Faiza; Tariq, Muhammad; Ejaz, Sana; Saadat, Rashiqa (Biological and Clinical Sciences Research Journal, 2025)
Guillain-Barré Syndrome (GBS) is a rare and potentially life-threatening neurological disorder caused by an aberrant autoimmune response, leading to acute inflammation and damage to the peripheral nerves. Objective: The purpose of this study is to provide a comprehensive description of the impact of GBS on children, including functional disability and health-related quality of life, using the Hughes score. Methodology: This Cross-sectional observational study was conducted in the inpatient and outpatient departments of the Pakistan Institute of Medical Sciences Children's Hospital, Islamabad. Seventy-four children aged 1- 12 with GBS were recruited and followed for 1 year. Clinical characteristics of the disease, functional disability score, and HRQOL were reported at 3 and 6 months. Results: The Study showed a male predominance (78.4%) and the majority aged < 5 years (47.3%). Seasonal variation revealed the highest incidence during winter (62.2%), followed by summer (18.9%). Preceding symptoms included upper respiratory tract infections (35.1%) and diarrhea (18.9%); the rest of the children had no preceding risk factors. The clinical presentation of Guillain-Barré Syndrome (GBS) in the study cohort was dominated by limb weakness (100%) and areflexia (100%), with muscle pain also being prevalent (83.8%). Complications included cranial nerve palsies (41.9%) and autonomic instability (55.4%). At discharge, 50% required walking assistance, and 44.6% were bedridden or chair-bound. Over six months, significant functional improvements were observed, with 86.1% having normal function and only 8.3% still needing walking assistance. Health-related quality of life assessments showed marked physical, emotional, and social enhancements over three and six months. However, two patients (2.7%) experienced rapid disease progression leading to death, underscoring the severity of GBS despite overall positive outcomes. Conclusion: It is concluded that Guillain-Barré Syndrome (GBS) significantly impacts the health-related quality of life (HRQOL) in children, affecting their physical, emotional, and social well-being.